Optically Controlled Magnetization and Magnetoelectric Effect in Organic Multiferroic Heterojunction. Issue 24 (4th October 2017) - Wei, Mengmeng; Niu, Mengsi; Bi, Pengqing; Hao, Xiaotao; Ren, Shenqiang; Xie, Shijie; Qin, Wei
Abstract: The organic multiferroic effect receives increasing attention in organic electronics. Recently, the renaissance of organic multiferroics has yielded in a deep understanding of organic magnetism and magnetoelectric coupling. Here, through fabricating polythiophene nanowire/CH3 NH3 PbBr3 multiferroic heterojunction, the origin of organic magnetism, optically controlled magnetization, and magnetoelectric coupling with optical approach is studied. Specifically, the optical approach utilizes double beam 355 and 607 nm excitations to separately operate the CH3 NH3 PbBr3 and polythiophene nanowire layers. This double‐beam‐light approach allows to elucidate the effects of photogenerated charges on organic magnetism and magnetoelectric coupling effect. It is found that magnetization and magnetoelectric coupling of polythiophene nanowire/CH3 NH3 PbBr3 heterojunction can be effectively tuned through the photoexcitation of CH3 NH3 PbBr3, rather than photoexcitation of polythiophene nanowire phase, which has been further confirmed by electron spin resonance. Furthermore, the dominated factors are discussed to reveal room‐temperature magnetization in organics. This work provides a strategy for optically controlled organic magnetism and magnetoelectric effect in charge transfer heterojunction. Abstract : In polythiophene nanowire (PT‐nw)/CH3 NH3 PbBr3 heterojunction, under 355 nm light illumination, charge transferring between PT‐nw and CH3 NH3 PbBr3 breaks a closed‐shell structure to form an open‐shell structure, in which room temperature magnetism can be observed. However, the closed‐shell structure is kept when applying 607 nm light illumination. In this case, no magnetism is observed in PT‐nw/CH3 NH3 PbBr3 heterojunction.